Identification of missense MAB21L1 variants in microphthalmia and aniridia. Issue 7 (24th May 2021) - Seese, Sarah E.; Reis, Linda M.; Deml, Brett; Griffith, Christopher; Reich, Adi; Jamieson, Robyn V.; Semina, Elena V.
Abstract: Microphthalmia, coloboma, and aniridia are congenital ocular phenotypes with a strong genetic component but often unknown cause. We present a likely causative novel variant in MAB21L1, c.152G>T p.(Arg51Leu), in two family members with microphthalmia and aniridia, as well as novel or rare compound heterozygous variants of uncertain significance, c.184C>T p.(Arg62Cys)/c.‐68T>C, and c.658G>C p.(Gly220Arg)/c.*529A>G, in two additional probands with microphthalmia, coloboma and/or cataracts. All variants were predicted as damaging by in silico programs. In vitro studies of coding variants revealed normal subcellular localization but variable stability for the corresponding mutant proteins. In vivo complementation assays using the zebrafish mab21l2 Q48Sfs*5 loss‐of‐function line demonstrated that though overexpression of wild‐type MAB21L1 messenger RNA (mRNA) compensated for the loss of mab21l2, none of the coding variant mRNAs produced a statistically significant rescue, with p.(Arg51Leu) showing the highest degree of functional deficiency. Dominant variants in a close homolog of MAB21L1, MAB21L2, have been associated with microphthalmia and/or coloboma and repeatedly involved the same Arg51 residue, further supporting its pathogenicity. The possible role of p.(Arg62Cys) and p.(Gly220Arg) in microphthalmia is similarly supported by the observed functional defects, with or without an additional impact from noncoding MAB21L1 variants identified in each patient. This study suggests a broader spectrum of MAB21L1 ‐associated disease. Abstract : MAB21L1 alleles in microphthalmia and aniridia.